Dreamtime Painters - Waring, Rob.; National Geographic Society (U.S.) (Boston, Mass. : Heinle, Cengage Learning, 2008)
Australia's Aboriginal culture is one of the oldest in the world. Aboriginal people have painted pictures of a story called 'Dreamtime' for years. These paintings are famous and very valuable. What is the Dreamtime story? Who are the Dreamtime painters?
Footprint reading library with video material from National Geographic Digital Media --Cover
language bookfair2015
Keywords: Englischunterricht